Molybdates and tungstates sorption on organo-smectites as a process controlled by the type and amount of surfactant - Muir, Barbara; Andrunik, Damian; Bajda, Tomasz (Geology, Geophysics and Environment, 2016)
Modification of a smectite with organic surfactants leads to the formation of an organo-mineral complex characterized by a positive charged (Bajda et al, 2015). The process involves the exchange of naturally occurring cations, eg. Ca2+, Mg2+, Na+, K+ by large organic cations of surfactants. This alteration makes it possible to use organo-smectites as sorbents to remove anionic forms of Mo(VI) and W(VI) from aqueous solutions. The concentration of molybdenum in the environment is significantly enhanced by anthropogenic inputs from coal-resource development, fly ash, sewage sludge and hard-rock mining activity (Kalembkiewicz, Sočo, 2009). W(VI) is released to the environment through its use in winter tires or by its applications in industry e.g. enriches alloys or electrotechnics (Gustafsson, 2003). The environmental behavior of molybdenum and tungsten once they dissolve becomes very complex as Mo(VI) and W(VI) anions occur as a monomer only in alkaline or neutral solutions. Bentonite from the Jelšovy Potok in Slovakia, rich in montmorillonite phase, was used in the sorption experiments (Bajda et al. 2015). Through the preparation of a series of experiments it was possible to define the impact of various surfactants, their amount and organo-smectites’ properties order on the sorption capacity and pH effect. Smectite has been modified with dodecyltrimethylammonium bromide (DDTMA), didodecyldimethylammonium bromide (DDDDMA), hexadecyltrimethylammonium bromide (HDTMA) and   dihexadecyldimethylammonium bromide (DHDDMA) in amounts of: 0.5, 1.0 and 2.0 of cation exchange capacity (CEC). Experiments of Mo(VI) and W(VI) sorption on organo-smectites were conducted under various concentrations of Mo(VI) and W(VI) (0 – 20 mM) and in wide range of pH’s (1-13). The effectiveness of modifications follows the order DDTMA-smectite-> HDTMA-smectite> DDDDMA-smectite > DHDDMA-smectite. The unmodified smectite did not remove Mo(VI) and W(VI) aninos from the aqueous solution at all. In the removal of Mo(VI), sorption efficiency follows the order: DDTMA-smectite > DDDDMA-smectite >  HDTMA-smectite> DHDDMA-smectite. In case of W(VI) the  efficiency of the removal can be place: DDDDMA-smectite> DDTMA-smectite> HDTMA-smectite> DHDDMA-smectite.  With an increasing concentration of Mo(VI) or W(VI) in the solutions, the sorption increases. The maximum sorption capacity in the removal of Mo(VI) was 1710 mmol Mo(VI)/kg in case of smectite modified with DDTMA at 0.5 CEC.  The best result of tungsten sorption was 5882 mmol W(VI)/kg and it was obtained for DDDDMA-smectite (0.5 CEC). Results showed that the sorption is more effective at a lower pH, in both Mo(VI) and W(VI) removal. The smectite modified with surfactant with double carbon chain (DDDDMA, DHDDMA) proved to be a better sorbent. With an increasing amount of surfactant attached to the smectite, the sorption efficiency increases.